Fortalecimiento de potencialidades ambientales mediante la aplicación de educación ambiental en el comedor adonai iglesia asambleas de Dios del Perú - Gómez Rlos, Llna Rosaura (2015)
The present research had aim to strengthen environmental potential through the implementation of envíronmental education in the díning room ADONAI Assemblies of God Church Pen.i of Moyobamba. In this sense, they were considered as indicators of the potentíal for disposal of solid waste on site, the care and conservation of water and food hygíene. Accordíng to the líterature review the research hypothesis under the assumption that if applíed environmental education was formulated, then managed to strengthen envíronmental potentíal of mothers dining ADONAI. In terms of methodology, the rate applied research was conducted under a preexperimental design group whose mothers were given a pre and post-test to determine differences in strengthening their environmental potential. The test consisted of 15 items; of which 5 correspond to the treatment of solid waste, 5 to care and conservatíon of water and 5 with respect to food hygiene. As for the hypothesis test for verification test corresponding to the distríbution of student with a confidence level of 95% we were used paired difference, concluding that the ímplementation of environmental educatíon workshops mothers of dining ADONAI Assemblies of God Church Peru able to strengthen their environmental potentiaL Also, before the experíment mothers showed poor level of knowledge regarding the disposal of solíd waste, water care and food hygíene, a situatíon that was reversed by applying workshops because after the experiment mothers They showed a good level whereby the efficiency of envíronmental education is evident.